Auf den Schultern des EU-Projektes gegen den „Status Quo“: Autoritärer Populismus in der Türkei und seine Krise - Gehring, Axel (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2018)
The article discusses the rise of authoritarian populism in the context of Turkeys neoliberalisation experience since 1980. For long time, populist politics in Turkey successfully claimed to be the voice of the suppressed against the ruling. In fact, they used an oppositional political language meanwhile processing the material interests of the hegemonic forces. Despite receiving considerable support, particularly from the European public, authoritarian populism fell into an deep crises throughout the recent years – the result is it radicalisation which is often mistakenly debated as the start of populism in Turkey.